Budget Tracking Anggaran Percepatan Penurunan Stunting: Analisis Multisektoral di Kabupaten Tuban - Setyaningsih, Yuni (Institut Teknologi Sepuluh Nopember, 2025)
Stunting remains an alarming problem in Indonesia, with profound implications for human capital development and long-term economic productivity. Despite the national government’s commitment, including Presidential Regulation No. 72/2021, inefficiencies in local budget execution continue to challenge targeted outcomes. This study aimed to track stunting-related budgets in Tuban Regency between 2021 and 2022, with a focus on allocation trends, sectoral involvement, and realization performance across specific and sensitive interventions. Budget allocations for stunting reduction increased sharply from IDR 17.5 billion in 2021 to IDR 51.1 billion in 2022 (a 192% increase), with participating government offices expanding from 4 to 9. The Health Department remained the lead implementer, implementing IDR 17.6 billion in 2022, or 34.5% of the total stunting-related budget with community nutrition services absorbed most of the budget. Meanwhile, the public works spent IDR 10.6 billion for rural water infrastructure, reinforcing the importance of WASH in sensitive interventions. The education sector experienced a threefold increase, yet its share remained under 0.5% of the total. While the environmental sector emphasized infrastructure-based waste management. These findings highlight fiscal expansion yet persistent implementation gaps. It is essential to strengthen budget tagging, intersectoral collaboration, and evidence-based planning to optimize the impact of increased investments in stunting reduction